Physical activity and other forms of spending free time by first-year nursing students depending on their age - Agnieszka Dmitruk; Wojciech Hołub (Rozprawy Społeczne)
Abstract The aim of the study was to assess the level of physical activity and other forms of spending free time among nursing students depending on the age of the respondents.